Natural justice in the armed forces: an appraisal of Section 9 of The Armed Forces Act 1972 / Anwar Zamani Jusop, Abdul Jalil Salam Muhamad and Mohd Faizal Abdullah - Jusop, Anwar Zamani; Muhamad, Abdul Jalil Salam; Abdullah, Mohd Faizal (2007)
Mc Cardie J in Heddon v Evan observed that, “Discipline is the soul of the Army. It is the basis of all military efficiency. The dignity and self respect of officers and privates alike are based upon it. The officer who does not enforce it would lose the respect of his men. The private who does not cheerfully submit to it is unworthy of our high military traditions. National safety depended upon the Armed Forces of the people. The power of those forces rest upon the maintenance of discipline. The plainest patriotism calls for its enforcement on the one hand and a ready submission to its requirements on the other hand". The Armed Forces came into existence with a strong and a strict discipline that must be abided by its members because without discipline, orders from the superior will be taken for granted and with a very much question or justification. Therefore the different set rule of law is needed to promote good order, high morale and discipline among their personnel. Therefore, the military law is a unique set of laws. It is applicable during peace and war. Someone would only be able to condemn the application of military law, one could only doing that after attaining a basic knowledge about military jurisprudence. Therefore, this research is to make public to be conversant or posses some knowledge from this wide cover area of military law.